2001
DOI: 10.1071/ar01015
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock influences postharvest anthracnose development in 'Hass' avocado

Abstract: Rootstock studies conducted on ‘Hass’ avocado found that rootstock had a significant impact on postharvest anthracnose susceptibility. This is the first record of such an effect for avocado. The severity and incidence of anthracnose was significantly lower on ‘Hass’ grafted to ‘Velvick’ Guatemalan seedling rootstock compared with the ‘Duke 6’ Mexican seedling rootstock. Differences in anthracnose susceptibility were related to significant differences in concentrations of antifungal dienes in the leaves and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In general, Guatemalan rootstocks (i.e., the G755 series, and G1033) had higher Ca and Mg, but lower N, than the Mexican rootstocks. Willingham et al (2001) also found that a Guatemalan rootstock had lower leaf N than a Mexican rootstock. Haas (1950a,b) found that seedling Guatemalan-race rootstocks had higher Ca than seedling Mexican-race rootstocks.…”
Section: Nutrient Analysismentioning
confidence: 91%
“…In general, Guatemalan rootstocks (i.e., the G755 series, and G1033) had higher Ca and Mg, but lower N, than the Mexican rootstocks. Willingham et al (2001) also found that a Guatemalan rootstock had lower leaf N than a Mexican rootstock. Haas (1950a,b) found that seedling Guatemalan-race rootstocks had higher Ca than seedling Mexican-race rootstocks.…”
Section: Nutrient Analysismentioning
confidence: 91%
“…Similar season or site effects on the correlations between Hass fruit quality attributes and flesh Ca, Mg, and K concentrations have been observed in New Zealand (Thorp et al 1997) and Australia (Hofman et al 2002;Vuthapanich 2001), with some sites showing strong correlations between fruit mineral concentrations and fruit quality in some years, but not in other years or in other sites. As the avocado industry in Australia is currently based on seedling rootstocks of unknown origin, it has been suggested that rootstocks may be a major contributing factor in the high between-tree variability in avocado quality and fruit minerals, and may present an important mechanism to improve avocado quality (Willingham et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Scion leaf concentrations of K, N and Mg can also be affected by rootstock race. Recent reports suggest that avocado rootstock can also affect fruit Ca concentration, the ratio of (Ca + Mg):K in the fruit, and fruit quality (Willingham et al 2001;Marques et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Anthracnose is a serious post-harvest fungal disease in avocado that leads to rotting of the fruit. Willingham et al (2001) tested ‘Hass’ scion on two rootstocks for their influence on anthracnose. After post-harvest ripening at 22 °C, fruit from 3.5- and 8-year-old trees demonstrated significant differences in both disease incidence and severity.…”
Section: Physiological Traitsmentioning
confidence: 99%